A high-temperature resistant high-strength grouting material specially used in steel plants
By using a combination of modified carbon fiber and steel fiber in the grouting material, the problem of insufficient compressive strength and high-temperature resistance of grouting materials in high-temperature environments is solved, and the efficient compressive resistance and high-temperature stability of the material is achieved.
Patent Information
- Application Number
- CN202411854967.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing grouting materials have insufficient compressive strength and high temperature resistance under high temperature environments, resulting in cracking or crushing, unable to effectively support the equipment or structure, affecting stability and normal use.
A high-temperature resistant high-strength grouting material for steel mills is adopted, including cement, aggregate, active mineral blend, modified carbon fiber and steel fiber. The carbon fiber is modified by modifiers to enhance its dispersion and binding strength in the cement matrix, and combine the synergistic effect of steel fibers to buffer and disperse heat stress.
The compressive strength and high temperature resistance of grouting materials are significantly improved, ensuring the structural stability of the material at high temperatures, avoiding local damage, and meeting the application needs of steel plants and other high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a high-temperature resistant high-strength grouting material specially used in steel plants. Background Art
[0002] Grouting materials are prepared by cement, aggregate, admixture and mineral admixture in a certain proportion. After adding water and stirring, they have good fluidity. They can be poured into various gaps, holes or used for structural reinforcement during construction. After hardening, they can provide high strength and good durability. An inorganic or organic composite material. At present, with the development of industrial fields such as chemical industry, metallurgy, and building materials, the scope of application of grouting materials is becoming wider and wider. For example, projects in high temperature environments such as steel plant converter tracks, kiln tracks, foundation cushions of heat load equipment, and secondary pouring layers of heat radiation resistant environment building structures all require grouting materials. However, ordinary grouting materials cannot meet the requirements of compressive strength and high temperature resistance. Ordinary grouting materials will crack or even break under high temperature, and then cannot effectively support the upper equipment or structure, affecting the overall stability and normal use. Therefore, it is very necessary to develop a grouting material with high compressive strength and high temperature resistance. Summary of the invention
[0003] The invention provides a high-strength high-temperature resistant grouting material specially used in steel plants, which solves the problems of low compressive strength and low high-temperature resistance of the grouting material in the related art.
[0004] The technical scheme of the present invention is as follows: The present invention proposes a high-temperature resistant high-strength grouting material specially used in steel plants, comprising the following raw materials in parts by weight: 40-45 parts of cement, 35-45 parts of aggregate, 4-8 parts of active mineral admixtures, 0.2-0.5 parts of early strength agent, 0.05-0.1 parts of retarder, 0.03-0.04 parts of plastic expansion agent, 0.3-0.5 parts of water reducer, 0.05-0.07 parts of defoaming agent, 0.02-0.05 parts of preservative, and 0.2-0.25 parts of fiber; the fiber comprises modified carbon fiber, and the modified carbon fiber is obtained by modifying carbon fiber with a modifier, and the modifier is a naphthylamine sulfonic acid compound.
[0005] As a further technical solution, the naphthylamine sulfonic acid compound includes one or more of 2-naphthylamine-3,6,8-trisulfonic acid, 2-naphthylamine-4,8-disulfonic acid, and 4-aminonaphthalene-1-sulfonic acid.
[0006] As a further technical solution, the preparation method of the modified carbon fiber comprises the following steps: dispersing the modifier in a solvent, adding the activated carbon fiber for modification, filtering and drying to obtain the modified carbon fiber.
[0007] As a further technical solution, the method for preparing the activated carbon fiber comprises the following steps: placing the carbon fiber in a nitric acid solution for activation, and drying to obtain the activated carbon fiber.
[0008] As a further technical solution, the activation time is 1-2 hours, the activation temperature is 60-80°C, the nitric acid solution is a 65wt% concentrated nitric acid solution, and the mass ratio of the carbon fiber to the concentrated nitric acid solution is 1:10.
[0009] As a further technical solution, the modification temperature is 40-50°C, and the modification time is 6-8h.
[0010] As a further technical solution, the mass ratio of the carbon fiber to the solvent is 1:10, and the solvent is dimethyl sulfoxide.
[0011] As a further technical solution, the raw material of the modified carbon fiber includes a modifier and carbon fiber in a mass ratio of 4 to 5:50.
[0012] As a further technical solution, the fiber also includes steel fiber, and the mass ratio of the modified carbon fiber to the steel fiber is 4~6:5.
[0013] As a further technical solution, the steel fiber is composed of 310# steel fiber and 330# steel fiber, and the mass ratio of the 310# steel fiber to the 330# steel fiber is 2~3:1.
[0014] In the present invention, 310# steel fiber and 330# steel fiber are used to form a steel fiber system, and the synergistic effect of the two is brought into play to effectively buffer and disperse thermal stress, prevent local damage caused by concentrated thermal stress, keep the overall structure of the material relatively stable at high temperature, and further improve the compressive strength and high temperature resistance of the grouting material.
[0015] As a further technical solution, the aggregate is composed of graded quartz sand and high-alumina aggregate in a mass ratio of 1:1, the particle size of the graded quartz sand is 10~100 mesh, and the graded quartz sand is composed of 10~40 mesh quartz sand, 40~70 mesh quartz sand, and 70~100 mesh quartz sand in a mass ratio of 4:3:3.
[0016] As a further technical solution, the active mineral admixture consists of silicon micropowder, calcium carbonate and metakaolin.
[0017] As a further technical solution, the mass ratio of the silicon micropowder, calcium carbonate and metakaolin is 5:2:3.
[0018] As a further technical solution, the early strength agent includes one or more of calcium formate, sodium humate, and potassium aluminum silicate.
[0019] As a further technical solution, the retarder includes one or more of sodium gluconate, tartaric acid, and citrate.
[0020] As a further technical solution, the cement is silicate cement P·O42.5.
[0021] As a further technical solution, the water reducer is a polycarboxylic acid high-efficiency water reducer.
[0022] As a further technical solution, the defoaming agent is a silicone powder defoaming agent.
[0023] As a further technical solution, the plastic expansion agent is plastic expansion agent EP-2.
[0024] The present invention also provides a method for preparing a high-temperature resistant high-strength grouting material specially used in steel plants, comprising the following steps:
[0025] S1. Weigh cement, aggregate, active mineral admixture, and fiber, mix them evenly, and obtain No. Ⅰ powder;
[0026] S2, weigh the early strength agent, retarder, plastic expansion agent, water reducing agent, defoaming agent, and preservative, mix them evenly, and obtain No. II powder;
[0027] S3. Evenly mix powder No. Ⅰ and powder No. Ⅱ, add water, and stir evenly to obtain high-strength grouting material.
[0028] As a further technical solution, the mass ratio of the No. Ⅰ powder and the No. Ⅱ powder to water is 1:0.12~0.13.
[0029] As a further technical solution, the stirring in S3 is carried out twice, the speed of the first stirring is 100-150 r / min, the time of the first stirring is 30-60 s, the speed of the second stirring is 800-1200 r / min, and the time of the second stirring is 2-4 min.
[0030] The working principle and beneficial effects of the present invention are:
[0031] In the present invention, the combined effect of cement, active mineral admixtures, early strength agents, etc. is utilized to effectively improve the early strength of the grouting material. At the same time, the active mineral admixtures and water reducers cooperate with each other to further reduce the water consumption. The carbon fibers are modified by using naphthylamine sulfonic acid compounds to enhance the dispersibility and bonding strength of the modified carbon fibers in the cement matrix, effectively resisting the thermal shock of high temperature on the carbon fibers, thereby improving not only the compressive strength of the grouting material, but also the high temperature resistance of the grouting material. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following examples and comparative examples:
[0034] Cement: Ordinary Portland Cement P·O42.5;
[0035] Graded quartz sand: particle size is 10~100 mesh, composed of 10~40 mesh quartz sand, 40~70 mesh quartz sand, 70~100 mesh quartz sand in a mass ratio of 4:3:3;
[0036] High alumina aggregate: average particle size is 0~3mm;
[0037] Silica powder: average particle size is 50~100nm;
[0038] Calcium carbonate: average particle size is 20nm;
[0039] Metakaolin: average particle size is 600 mesh;
[0040] Preservative: Model: H505, manufacturer: Kehui (Shanghai) New Material Technology Co., Ltd.;
[0041] Polycarboxylic acid high-efficiency water reducing agent: model GH-JSJ, manufacturer is Shandong Gaochuang Hengda New Building Materials Technology Co., Ltd.;
[0042] Plastic expansion agent: model EP-2;
[0043] Silicone powder defoamer: model P803;
[0044] Carbon fiber: diameter 0.15~0.2mm, length 3mm;
[0045] 310# steel fiber: diameter is 0.15~0.2mm, length is 3mm;
[0046] 330# steel fiber: diameter is 0.15~0.2mm and length is 3mm.
[0047] Example 1
[0048] The preparation method of modified carbon fiber comprises the following steps: adding 5 parts of carbon fiber to 50 parts of 65wt% concentrated nitric acid solution, heating to 60°C, stirring for 2h, filtering and drying to obtain activated carbon fiber, dispersing 0.4 parts of 4-aminonaphthalene-1-sulfonic acid in 50 parts of dimethyl sulfoxide, adding the activated carbon fiber, heating to 40°C for modification for 8h, filtering and drying to obtain modified carbon fiber;
[0049] A method for preparing a high-temperature resistant high-strength grouting material specially used in a steel plant comprises the following steps:
[0050] S1. Weigh 40 parts of cement, 35 parts of aggregate, 4 parts of active mineral admixture, and 0.2 parts of fiber, mix them evenly, and obtain powder No. Ⅰ, wherein the aggregate is composed of graded quartz sand and high-alumina aggregate in a mass ratio of 1:1, the active mineral admixture is composed of silicon powder, calcium carbonate, and metakaolin in a mass ratio of 5:2:3, and the fiber is modified carbon fiber;
[0051] S2, weigh 0.2 parts of calcium formate, 0.05 parts of sodium gluconate, 0.03 parts of plastic expansion agent, 0.3 parts of polycarboxylic acid high-efficiency water reducing agent, 0.05 parts of silicone powder defoaming agent, and 0.02 parts of preservative, mix well to obtain powder No. II;
[0052] S3. Evenly mix powder No. Ⅰ and powder No. Ⅱ, add water, stir at 100 r / min for 60 seconds, and then stir at 800 r / min for 4 minutes to obtain high-strength grouting material, in which the mass ratio of powder No. Ⅰ and powder No. Ⅱ to water is 1:0.12.
[0053] Example 2
[0054] The preparation method of modified carbon fiber comprises the following steps: adding 5 parts of carbon fiber to 50 parts of 65wt% concentrated nitric acid solution, heating to 70°C, stirring for 1.5 hours, filtering and drying to obtain activated carbon fiber, dispersing 0.4 parts of 4-aminonaphthalene-1-sulfonic acid in 50 parts of dimethyl sulfoxide, adding the activated carbon fiber, heating to 45°C for modification for 7 hours, filtering and drying to obtain modified carbon fiber;
[0055] A method for preparing a high-temperature resistant high-strength grouting material specially used in a steel plant comprises the following steps:
[0056] S1. Weigh 42 parts of cement, 40 parts of aggregate, 6 parts of active mineral admixture, and 0.23 parts of fiber, mix them evenly, and obtain powder No. Ⅰ, wherein the aggregate is composed of graded quartz sand and high-alumina aggregate in a mass ratio of 1:1, the active mineral admixture is composed of silicon powder, calcium carbonate, and metakaolin in a mass ratio of 5:2:3, and the fiber is modified carbon fiber;
[0057] S2, weigh 0.3 parts of calcium formate, 0.08 parts of sodium gluconate, 0.035 parts of plastic expansion agent, 0.4 parts of polycarboxylic acid high-efficiency water reducing agent, 0.06 parts of organosilicon powder defoaming agent, and 0.03 parts of preservative, mix well to obtain powder No. II;
[0058] S3. Evenly mix powder No. Ⅰ and powder No. Ⅱ, add water, stir at 120 r / min for 45 seconds, and then stir at 1000 r / min for 3 minutes to obtain high-strength grouting material, in which the mass ratio of powder No. Ⅰ and powder No. Ⅱ to water is 1:0.125.
[0059] Example 3
[0060] The preparation method of modified carbon fiber comprises the following steps: adding 5 parts of carbon fiber to 50 parts of 65wt% concentrated nitric acid solution, heating to 80°C, stirring for 1 hour, filtering and drying to obtain activated carbon fiber, dispersing 0.4 parts of 4-aminonaphthalene-1-sulfonic acid in 50 parts of dimethyl sulfoxide, adding the activated carbon fiber, heating to 50°C for modification for 6 hours, filtering and drying to obtain modified carbon fiber;
[0061] A method for preparing a high-temperature resistant high-strength grouting material specially used in a steel plant comprises the following steps:
[0062] S1. Weigh 45 parts of cement, 45 parts of aggregate, 8 parts of active mineral admixture, and 0.25 parts of fiber, mix them evenly, and obtain powder No. Ⅰ, wherein the aggregate is composed of graded quartz sand and high-alumina aggregate in a mass ratio of 1:1, the active mineral admixture is composed of silicon micropowder, calcium carbonate, and metakaolin in a mass ratio of 5:2:3, and the fiber is modified carbon fiber;
[0063] S2, weigh 0.5 parts of calcium formate, 0.1 parts of sodium gluconate, 0.04 parts of plastic expansion agent EP-2, 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, 0.07 parts of silicone powder defoaming agent, and 0.05 parts of preservative, mix well to obtain powder No. II;
[0064] S3. Evenly mix powder No. Ⅰ and powder No. Ⅱ, add water, stir at 150 r / min for 30 seconds, and then stir at 1200 r / min for 2 minutes to obtain high-strength grouting material, in which the mass ratio of powder No. Ⅰ and powder No. Ⅱ to water is 1:0.13.
[0065] Example 4
[0066] Compared with Example 1, the difference in Example 4 is that the added amount of 4-aminonaphthalene-1-sulfonic acid is 0.5 parts.
[0067] Example 5
[0068] Compared with Example 4, Example 5 is different in that 4-aminonaphthalene-1-sulfonic acid is replaced by an equal amount of 2-naphthylamine-4,8-disulfonic acid.
[0069] Example 6
[0070] Compared with Example 4, Example 6 is different in that 4-aminonaphthalene-1-sulfonic acid is replaced by an equal amount of 2-naphthylamine-3,6,8-trisulfonic acid.
[0071] Example 7
[0072] Compared with Example 5, the difference of Example 7 is that the fiber is composed of the modified carbon fiber and steel fiber prepared in Example 1 in a mass ratio of 4:5, wherein the steel fiber is 310# steel fiber.
[0073] Example 8
[0074] Compared with Example 7, the difference of Example 8 is that the fiber is composed of the modified carbon fiber and steel fiber prepared in Example 1 in a mass ratio of 1:1, wherein the steel fiber is 310# steel fiber.
[0075] Example 9
[0076] Compared with Example 7, the difference of Example 9 is that the fiber is composed of the modified carbon fiber and steel fiber prepared in Example 1 in a mass ratio of 6:5, wherein the steel fiber is 310# steel fiber.
[0077] Example 10
[0078] Compared with Example 8, the difference of Example 10 is that the 310# steel fiber is replaced by an equal amount of 330# steel fiber.
[0079] Embodiment 11
[0080] Compared with Example 8, the difference of Example 11 is that the steel fiber consists of 310# steel fiber and 330# steel fiber in a mass ratio of 2:1.
[0081] Example 12
[0082] Compared with Example 8, the difference of Example 12 is that the steel fiber consists of 310# steel fiber and 330# steel fiber in a mass ratio of 3:1.
[0083] Comparative Example 1
[0084] Compared with Example 1, the difference in Comparative Example 1 is that the modified carbon fiber is replaced by an equal amount of carbon fiber.
[0085] The high-strength grouting materials prepared in Examples 1 to 12 and Comparative Example 1 were tested according to the following method:
[0086] 1. Compressive strength: The sample is made into a prism with a size of 40mm×40mm×160mm. According to the compressive strength test method specified in Article A.0.5 of GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials", the compressive strength of the sample is tested after 28 days of curing.
[0087] 2. Compressive strength ratio: According to the compressive strength ratio test method specified in Article A.0.8 of GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials", the compressive strength ratio of the test sample is tested at a specified temperature of 800°C.
[0088] The test results are shown in Table 1 below:
[0089] Table 1 Performance test results of high-strength grouting materials prepared in Examples 1 to 12 and Comparative Example 1
[0090]
[0091] Compared with Comparative Example 1, Example 1 adds modified carbon fibers modified by naphthylaminesulfonic acid compounds. As a result, the compressive strength and compressive strength ratio of Example 1 are higher than those of Comparative Example 1, indicating that the addition of modified carbon fibers can improve the compressive strength and high temperature resistance of the grouting material.
[0092] Different types of naphthylaminesulfonic acid compounds were added to modify the carbon fibers in Examples 4 to 6. As a result, the compressive strength and compressive strength ratio of Example 5 were higher than those of Examples 4 and 6, indicating that when the modifier was 2-naphthylamine-4,8-disulfonic acid, the obtained grouting material had better compressive strength and high temperature resistance.
[0093] Compared with Example 5, Examples 7 to 9 simultaneously added modified carbon fiber and steel fiber. As a result, the compressive strength and compressive strength ratio of Examples 7 to 9 were higher than those of Example 5, indicating that the modified carbon fiber and steel fiber play a synergistic role and can further improve the compressive strength and high temperature resistance of the grouting material.
[0094] In Examples 7 to 9, modified carbon fibers and steel fibers were added in different mass ratios. As a result, the compressive strength and compressive strength ratio of Example 8 were higher than those of Examples 7 and 9, indicating that when the mass ratio of modified carbon fibers to steel fibers was 1:1, the obtained grouting material had better compressive strength and high temperature resistance.
[0095] Compared with Examples 8 and 10, Examples 11 and 12 simultaneously added 310# steel fiber and 330# steel fiber as steel fibers. As a result, the compressive strength and compressive strength ratio of Examples 11 and 12 were higher than those of Examples 8 and 10, indicating that 310# steel fiber and 330# steel fiber play a synergistic role and can further improve the compressive strength and high temperature resistance of the grouting material.
[0096] According to the test method specified in GB / T50448-2015 "Technical Specification for Application of Cement-based Grouting Materials", the high-strength grouting materials prepared in Examples 1 to 12 and Comparative Example 1 were tested as follows.
[0097] The test results are shown in Table 2 below:
[0098] Table 2 Performance test results of high-strength grouting materials prepared in Examples 1 to 12 and Comparative Example 1
[0099]
[0100] It can be seen from Table 2 that the maximum aggregate particle size, fluidity, compressive strength, vertical expansion rate, water seepage rate and 800°C thermal shock resistance of the high-strength grouting materials prepared in Examples 1 to 12 and Comparative Example 1 all meet the test standards.
[0101] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-temperature resistant high-strength grouting material specially used in steel plants, characterized in that: The invention comprises the following raw materials in parts by weight: 40-45 parts of cement, 35-45 parts of aggregate, 4-8 parts of active mineral admixture, 0.2-0.5 parts of early strength agent, 0.05-0.1 parts of retarder, 0.03-0.04 parts of plastic expansion agent, 0.3-0.5 parts of water reducing agent, 0.05-0.07 parts of defoaming agent, 0.02-0.05 parts of preservative, and 0.2-0.25 parts of fiber; the fiber comprises modified carbon fiber, the modified carbon fiber is obtained by modifying carbon fiber with a modifier, and the modifier is a naphthylamine sulfonic acid compound; The naphthylamine sulfonic acid compound is 2-naphthylamine-4,8-disulfonic acid; The fibers further include steel fibers, and the mass ratio of the modified carbon fibers to the steel fibers is 4 to 6:5; The steel fiber consists of 310# steel fiber and 330# steel fiber, and the mass ratio of the 310# steel fiber to the 330# steel fiber is 2-3:
1.
2. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: dispersing a modifier in a solvent, adding the activated carbon fiber for modification, filtering and drying to obtain the modified carbon fiber.
3. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The raw materials of the modified carbon fiber include a modifier and carbon fiber in a mass ratio of 4 to 5:
50.
4. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The aggregate consists of graded quartz sand and high-alumina aggregate in a mass ratio of 1:1, the particle size of the graded quartz sand is 10-100 meshes, and the graded quartz sand consists of 10-40 mesh quartz sand, 40-70 mesh quartz sand, and 70-100 mesh quartz sand in a mass ratio of 4:3:
3.
5. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The active mineral admixture consists of silicon micropowder, calcium carbonate and metakaolin.
6. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The early strength agent includes one or more of calcium formate, sodium humate, and potassium aluminum silicate.
7. The high-temperature resistant high-strength grouting material for steel mills according to claim 1, characterized in that: The retarder includes one or more of sodium gluconate, tartaric acid and citrate.
Citation Information
Patent Citations
Cement-based high-temperature-resistant grouting material and preparation method thereof
CN107244858A